Community Support System-Based Health care for Children as Violence Victims during Pandemic - Sukoco, Bambang; Iksan, Muchamad; Wati, Dewi Eko; Bangsawan, Moh Indra; Diarti, Dewi Kusuma; Budiono, Arief (Open Access Macedonian Journal of Medical Sciences, 2022)
The Republic of Indonesia's 1945 Constitution Article 28B and the Law No. 35 of 2014 on Child Protection Article 13 clause (1) state that children have the right for protection against discriminative behaviors, economic and sexual exploitation, neglect, cruelty, violence, torture, injustice, and other wrongful treatments. This research aims: (1) to describe the violence to children, (2) to describe the community support system-based healthcare policy concept for children as violence victims. This is a normative legal research which is carried out by literature review and by analyzing secondary data. The approaches used are the statute approach and the conceptual approach. It uses the descriptive method, as it aims to clearly describe the various things related to the analyzed objects. The policies proposed in this research are those which are analyzed using the Fishbone model. The identification process is carried out by finding the main problem which affects the legal protection for children as violence victims in the Covid-19 pandemic era which is not yet optimum. It uses some indicators, which are: (1) policies; (2) regulations; (3) family; (4) education institutions; (5) the society which are described as small bones. Then, the big bones are the analysis which is not yet optimum. The research results show that during this pandemic, the violence towards children have drastically increased. On June 2020, there were 3.555 cases, which increased to 4.928 cases on July 2020. Because of that, the government needs to formulate an inter-sectoral child protection